What would you like to do?
What is x squared minus 3x minus 40?
What is the question? Do you want to factor 3x2 -x -2? If that is the question the answer is (3x + 2)(x-1)
X squared - 3x - 10 = 0 (x-5) (x+2) = 0 x - 5 = 0 x + 2 = 0 X= 5 x = -2
x³ + x² - 3x - 3 = (x + 1)(x + √3) (x - √3).
3x^2 - x^2 = (3 - 1)(x^2) = 2x^2 It is a good idea early one in math to think of things like this.. just like we can add or subtract numbers, we can add or sub…tracts x^2 or x^3 or squareroots of x... So think of 3x^2 as three (x^2)s...that is to say x^2 is something, like apples or oranges and you are just taking 3 or them and taking away one of them, so you have 2 of them.
(x - 6)(x + 9)
This quadratic expression cannot be factored because its discriminant is less than zero.
(x - 8)(x + 5)
well, i believe it goes like this (not certain) 25 is the only not prime number so... 3xcubed x squared -5 squared
This expression doesn't tell what 'x' has to be. In fact, 'x' can be anything. Your choice. Every time you change 'x', the expression becomes a different number. If this e…xpression were equal to something, then we could get some exercise figuring out what 'x' must be in order to make the equation true. But in its present form, it doesn't say anything, so there's nothing to be proven true or false. It's just a number that depends on what 'x' is.
3x2 -4 (x=3) 3(32)-4 3(9)-4 27-4=23
The expression does not have rational factors.
Do you mean: 3x2+x-14 = 0 If so the solutions are: x = 2 and x = -7/3 using the quadratic equation formula
3x2+x-2 = (3x-2)(x+1) when factored
3X = x2 - 2x subtract 3X from each side X2 - 5X = 0 factor out an X X(X - 5) = 0 = X = 0 --------or X = 5 --------
That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (1 plus or minus the square root of -47) divided by 6. x = 0.16666 + 1.14260910…0066840i = 1st root = r1 x = 0.16666 - 1.142609100066840i = 2nd root = r2 where i is the square root of negative one. Then factor as (x - r1)(x - r2) Or you can complete the square to transform the trinomial into the difference of the squares 3x2 - x + 4 factor out 3 = 3(x2 -(1/3)x + 4/3) add and subtract (1/6)2 = 3[x2 -(1/3)x + (1/6)2 - 1/36 + 4/3] simplify = 3[(x - 1/6)2 + 47/36] write 47/36 = - (-47/36) = - (√-1√47/6)2 = - (i√47/6)2 = 3[(x - 1/6)2 - (i√47/6)2] write the difference of the squares = 3[(x - 1/6) - (i√47/6)][(x - 1/6) + (i√47/6)] = 3[(x - (1 + i√47)/6)][(x - (1 - i√47)/6].